2017
DOI: 10.2217/pgs-2016-0164
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ Perceptions of Pharmacogenomics use in Psychiatry

Abstract: Most clinicians acknowledge the potential of pharmacogenomic testing in clinical practice. However, concerns with regard to its cost-effectiveness and the lack of clear guidelines are possible barriers to its clinical implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
69
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 19 publications
8
69
0
4
Order By: Relevance
“…However patients appear to be more willing to pay out-of-pocket if the disease associated with pharmacogenetic testing is high risk and the risk of recurrent acute coronary or cerebrovascular events associated with clopidogrel failures would certainly fall in this category [21]. Our finding that there is a high acceptance rate for the use of pharmacogenetics to guide treatment in patients with cardiovascular disease is consistent with studies conducted in other populations [10,15,19,22,23]. The utilization of precision medicine may improve drug adherence and result in a decrease in the overall cost of healthcare for patients by decreasing the occurrence of clinical events [24,25].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However patients appear to be more willing to pay out-of-pocket if the disease associated with pharmacogenetic testing is high risk and the risk of recurrent acute coronary or cerebrovascular events associated with clopidogrel failures would certainly fall in this category [21]. Our finding that there is a high acceptance rate for the use of pharmacogenetics to guide treatment in patients with cardiovascular disease is consistent with studies conducted in other populations [10,15,19,22,23]. The utilization of precision medicine may improve drug adherence and result in a decrease in the overall cost of healthcare for patients by decreasing the occurrence of clinical events [24,25].…”
Section: Discussionsupporting
confidence: 83%
“…There may also be social barriers towards genetic testing that may need to be taken into account as Asian patients may be apprehensive about the stigmas that are possibly associated with possessing a certain "defective" gene [14]. In our study, consistent with prior studies, female patients had less favorable attitudes towards pharmacogenetic testing and were more concerned about the negative impacts of precision medicine [14][15][16][17][18][19]. Subgroup analysis revealed that these statistically significant differences occurred more frequently in Korean females.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, these results are supported by a survey of the public's opinion toward PGx testing, which found that most U.S. adults were interested in PGx testing to assist with drug selection, medication dosing, and prediction of medication side effects [17]. The presence of skepticism pre-testing was similarly found among non-genotyped patients in another study that contrasted the views of patients who had or had not been genotyped [26]. The genotyped cohort reported a better understanding of PGx with greater recep-tiveness to its use by their provider.…”
Section: Discussionmentioning
confidence: 80%
“…A recent study29 surveying psychiatric pharmacists showed only 36% considered themselves knowledgeable in pharmacogenomics, and 80% worked at sites that did not offer the testing due to lack of funding. Another recent study30 was conducted in Singapore, which only routinely tests for HLA-B*1502 prior to carbamazepine initiation. Most responders in this study believe pharmacogenomic testing has potential in clinical practice but cost and lack of clear guidelines were identified as barriers (94.3% and 84.5%, respectively).…”
Section: Discussionmentioning
confidence: 99%